GAMBARAN STATUS GIZI IBU HAMIL PADA KEJADIAN BERAT BADAN LAHIR RENDAH (BBLR) DI RSUD WONOSARI TAHUN 2014 - Choirul Rizky Aulia; Endah Puji Astuti (Universitas Jenderal Achmad Yani Yogyakarta, 2015)
Background : Fetal mortality rate becomes the first indicator in defining child health grade and low birth weight is the primary cause of fetal still birth in Indonesia. Some of the low birth weight babies were delivered by pregnant mothers with poor nutrition that can be detected by measuring upper arm cycle, hemoglobin level in blood, and body mass index. Data that the researcher got indicated prevalence of low birth weight case in Yogyakarta as many as 4,48% with the highest prevalence located in Gunungkidul regency. Preliminary study identified 223 delivering mothers who delivered babies with low birth weight in 2014. Objective : To find out the description of nutritional status of pregnant mothers in low birth weight case in Wonosari general hospital 2014 Method : This was a quantitative descriptive study with retrospective approach which used secondary data of medical record that were low birth weight data during January-December 2014. The implementation of the study was implenented on 2-9July 2015. The number of respondent were 100 respondents that were selected through purposive sampling technique. Variable in this study was single variable and data analysis applied single variable analysis. Result : Nutritional status of pregnant mothers in low birth weight cases based on : LILA was that the majority of mothers suffered chronic energy deficiency (KEK) as many as 56 respondents (56,0%), Hemoglobin level was normal as many as 59 respondents (59,0%), body mass index was normal as many as 64 respondents (64,0%). Conclusion : The result indicated that nutritional status of pregnant mothers in low birth weight cases was risked by chronic energy deficiency (KEK). Key Word : Low Birth Weight, Nutritional status of Pregnant mother